PENGARUH KEPUASAN KERJA, MOTIVASI KERJA, DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION KARYAWAN DI RUMAH SAKIT BERSALIN (RSB) AVISENA - Sadikin, Mochamad Rizki; Junaedi, Junaedi; Syamsunasir, Syamsunasir; Yasmin, Yasmin (Jurnal Perspektif Manajerial dan Kewirausahaan (JPMK), 2023)
This study aims to examine and analyze the influence of job satisfaction, work motivation, and organizational commitment on turnover intention. A lesson from case of the desire of an employee to leave a company, specificly from AVISENA Maternity Hospital’s Employee perspective. The research was design by using conclusive, in causal type, with quantitative and survey methods. The sampling method used is saturation sampling and the data was analized by SEM-PLS with SmartPLS. Data was taken by giving self-administered questionnaire (SAQ) to 59 respondents. Respondents are AVISENA Maternity Hospital’s employee. The result shows that the job satisfaction, work motivation, and organizational commitment variable have a negative impact on turnover intention.